(untitled) (Bangladesh Heart Journal, 2024)
In this case report, a 29-year young male patient who presented with a history of right sided hemiparesis for 12 hours with no apparent cause. He showed no cough, palpitations, breathlessness, chest pain, syncope, or loss of vision. He had no relevant family history but had a history of two times admission in a National Neuroscience hospital for stroke. Echocardiography showed a freely mobile LV apical mass with hypokinetic apical septum and apex. He underwent successful removal of the mass via the LA roof. The postoperative TEE was normal. Histopathological examination of the resected mass revealed organized thrombus and patient had a satisfactory outcome. Bangladesh Heart Journal 2024; 39(1): 69-72